Comparing INTERGROWTH-21st Century and Hadlock growth standards to predict small for gestational age and short-term neonatal outcomes. (2nd June 2020) - Nwabuobi, Chinedu; Odibo, Linda; Camisasca-Lopina, Hannah; Leavitt, Karla; Tuuli, Methodius; Odibo, Anthony O.
Abstract: Objective: To compare the INTERGROWTH-21st Century growth standard to the Hadlock standard in predicting small for gestational age (SGA) and adverse neonatal outcomes. Method: This is a prospective cohort study on women with singleton gestations referred for fetal growth ultrasound between 26.0 and 36.6 weeks gestational age (GA). The primary outcome is prediction of neonatal SGA. Neonatal SGA was defined as birthweight <10th percentile for GA by Alexander chart. The discriminatory ability of the growth standards was compared using area under receiver operating characteristic curves (AUC). Results: Among 1054 patients who met inclusion criteria, 139 (13.2%) had neonatal SGA. The mean interval between estimated fetal weight and birthweight was 6.7 ± 3.1 weeks. Composite adverse neonatal outcome was seen in 300 (28.4%) patients. The sensitivity for identifying SGA neonates was higher for Hadlock compared with INTERGROWTH-21st standard (41.7 vs. 24.5%); AUC (95% CI) were 0.69 (0.65–0.73) and 0.62 (0.58–0.65), respectively. Both standards were comparable in predicting the composite adverse neonatal outcomes; AUC (95% CI) were 0.52 (0.50–0.53) and 0.52 (0.50–0.54), respectively; p  = .28. Conclusions: The Hadlock standard had a moderate but higher discriminatory ability for predicting neonatal SGA compared to the INTERGROWTH-21st project standard. However, the two standards were poor predictors of early adverse neonatal outcomes. Rationale: The Intergrowth-21st project was recently introduced with the goal of providing a universal benchmark for comparing growth across different ethnicity. We performed a prospective cohort study to compare the Intergrowth-21st standard with the commonly used Hadlock standard for predicting pregnancies at risk for neonatal SGA and adverse outcomes. Hadlock fetal growth standard is moderately superior at predicting neonatal SGA compared to the Intergrowth-21st standard. Both standards are poor at predicting adverse neonatal outcomes. These findings, however, need further validation.